Gerações no âmbito organizacional: o caso de uma entidade associativista de Nova Petrópolis - Weber, Andréia Zilles (My University, 2019)
Organizations are in a dynamic landscape, where survive the ones that are able to adapt to the frequent changes. The challenge in this scenario, which has been gaining organizational prominence, is a coexistence between generations within the labor market, thus needing to expand research on the subject in Brazil. It is in this bias, that the present study investigated how the Baby Boomer, X, Y and Z generations interfere in the organizational environment of an association located in Nova Petrópolis. Thus, to reach the proposed goal, the case study was carried out in an associative entity of Nova Petrópolis. The research is a qualitative approach and as a collection tool we used semi-structured interviews, individual, in-depth, non-participant observation and analysis of secondary data, making it possible to triangulate the data. Data analysis was performed based on the technique of content analysis. Through the research with the associative entity of Nova Petrópolis, it was possible to understand the individuals belonging to the Baby Boomer, X, Y and Z generations, to identify the generational characteristics and how they interfere in the organizational scope. The results found point to the existence of a good relationship between the professionals of the Baby Boomer, X, Y and Z generations in the work environment, however, it was identified the occurrence of conflicts and that impact on individual performance. The results also emphasized the importance of relativizing the topic of generations, since it encompasses characteristics and unique experiences of each individual. At the end, the limitations of the research and suggestions for future studies were presented. [resumo fornecido pelo autor]
As organizações encontram-se em um cenário dinâmico, onde sobrevive quem conseguir se adaptar às constantes mudanças. O desafio neste cenário, que vem ganhando destaque organizacional, é a convivência entre as gerações dentro do mercado de trabalho, necessitando assim, ampliar pesquisas referente ao tema no Brasil. É neste viés, que o presente estudo investigou de que forma as características das gerações Baby Boomer, X, Y e Z interferem no ambiente organizacional. Assim, para alcançar o objetivo proposto foi realizado um estudo de caso em uma entidade associativista de Nova Petrópolis. A pesquisa é de abordagem qualitativa e como instrumento de coleta foi utilizada entrevistas semiestruturada, individual, em profundidade, observação não participante e análise de dados secundários, possibilitando a triangulação dos dados. A análise de dados foi realizada com base na técnica de análise de conteúdo. Através da pesquisa junto a entidade associativista de Nova Petrópolis, foi possível a compreensão dos indivíduos pertencentes as gerações Baby Boomer, X, Y e Z, identificar as características geracionais e como elas interferem no âmbito organizacional. Os resultados encontrados apontam para a existência de um bom relacionamento entre os profissionais das gerações Baby Boomer, X, Y e Z no ambiente de trabalho, contudo, foi identificada a ocorrência de conflitos e que impactam sobre o desempenho individual. Os resultados também ressaltaram a importância de relativizar o tema gerações, pois engloba características e vivências singulares de cada indivíduo. Ao final, foram apresentadas a limitação da pesquisa e sugestões para futuros estudos. [resumo fornecido pelo autor]
Keywords: Geração X; Geração Y; Geração Z; Ambiente de trabalho; Associações, instituições, etc.